Robert Grosseteste and the pursuit of Religious and Scientific Learning in the Middle Ages - Cunningham, Jack P.; Hocknull, Mark.; SpringerLink (Online service) (Cham : Springer International Publishing(Imprint), 2016)
This book explores a wide range of topics relating to scientific and religious learning in the work of Bishop Robert Grosseteste (c. 1168-1253) and does so from various perspectives, including those of a twenty-first century scientists, historians and philosophers as well as several medievalists. In particular, it aims to contribute to our understanding of where to place Grosseteste in the history of science (against the background of the famous claim by A.C. Crombie that Grosseteste introduced what we now might call "experimental science") and to demonstrate that the polymathic world of the medieval scholar, who recognized no dichotomy in the pursuit of scientific and philosophical/theological understanding, has much to teach those of us in the modern world who wrestle with the vexed question of the relationship between science and religion. The book comprises an edited selection of the best papers presented at the 3rd International Robert Grosseteste Conference (2014) on the theme of scientific and religious learning, especially in the work of Grosseteste.
From the Contents: Grosseteste's Hexaemeron: the Order and Beauty of the Universe -- Medieval lessons for modern challenges to Science and Religion -- Greco- Arabic precursors of Grosseteste in the science of Optics -- The form of Corporeity and the Nomological image of Nature -- Religion, Philosophy and Science: Roger Bacon's Opus maius.
Keywords: History; Philosophy of mind; Cosmology